Influencing Factors of Foreign Film and TV Production Technologies Affect the Behavior of Sichuan Viewers in the Context of Mainland Media Entertainment Development - Xingyao Tang; Jacky Mong Kwan Watt (International Forum of Researchers and Lecturers, 2025)
As foreign films and television shows increasingly showcase superior production values, audiences in Sichuan have developed higher expectations regarding the quality of content they consume. This shift is primarily driven by exposure to advanced filming techniques, sophisticated storytelling, and high production standards seen in successful foreign media. This study examines how viewers become accustomed to these elevated standards, often favoring local productions that reflect the quality and innovation found in international offerings. This trend compels local media producers to enhance their production capabilities, adopting advanced technologies and techniques to meet the evolving demands of their audience. As a result, the integration of foreign production technologies not only improves the quality of local content but also influences viewer behavior, leading to a preference for productions that exhibit high artistic and technical standards. The relationship between foreign advanced production technologies and viewer preferences in Sichuan underscores a significant shift in the local media landscape. As audiences increasingly demand higher-quality content, local media must adapt by embracing technological advancements to enhance their productions and align with viewer expectations.